2002
DOI: 10.1046/j.1365-2427.2002.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in genetic structure of North American Bythotrephes populations following invasion from Lake Ladoga, Russia

Abstract: 1. We used allozyme electrophoresis to compare Bythotrephes longimanus (Crustacea: Onychopoda: Cercopagididae) from recently founded North American populations with those from native European populations, and to examine changes in genetic structure of North American populations over time. 2. The genetic structure of North American populations in 1996 was similar to that of European populations, because of the disappearance of founder effects which distinguished North American from European populations in 1989.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 28 publications
7
46
0
1
Order By: Relevance
“…trementosoides in the Mediterranean Sea, northern Europe, eastern North America, and in the South Pacific all possess markedly lower haplotype diversity relative to native populations in Japan (Provan et al, 2005). Similarly, introduced populations of Bythotrephes and Cercopagis in the Great Lakes have lower genetic diversity compared to native populations in Europe (Berg and Garton, 1994;Cristescu et al, 2001;Berg et al, 2002;Therriault et al, 2002a, b). Further, environmental differences between the introduced and source habitats could result in selection and further restriction of genetic diversity (Lee, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…trementosoides in the Mediterranean Sea, northern Europe, eastern North America, and in the South Pacific all possess markedly lower haplotype diversity relative to native populations in Japan (Provan et al, 2005). Similarly, introduced populations of Bythotrephes and Cercopagis in the Great Lakes have lower genetic diversity compared to native populations in Europe (Berg and Garton, 1994;Cristescu et al, 2001;Berg et al, 2002;Therriault et al, 2002a, b). Further, environmental differences between the introduced and source habitats could result in selection and further restriction of genetic diversity (Lee, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys of allozymes and mitochondrial DNA have identified similar levels of genetic diversity between source and invading populations of Dreissena mussels (Hebert et al, 1989;Marsden et al, 1995;Wilson et al, 1999b;Lewis et al, 2000) and bivalves in general (Duda, 1994;Holland, 2001), suggesting a lack of founder or selection effects. In contrast, reduced genetic diversity has been reported for other invading organisms including waterfleas, Bythotrephes longimanus and Cercopagis pengoi (Berg and Garton, 1994;Cristescu et al, 2001;Berg et al, 2002;Therriault et al, 2002a, b), the green alga Codium fragile spp. trementosoides (Provan et al, 2005) and the periwinkle Litorina saxatalis (Knight et al, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…Molecular genetic approaches offer a solution to this lack of information, enabling a determination of both the source regions of invasive species and the dispersal corridors employed during their range expansions. Despite this fact, only a few genetic studies have so far examined the source areas of aquatic invaders, their dispersal vectors, or the biological factors that prompt invasions (eg, Spidle et al, 1994;Havel et al, 2000;Cristescu et al, 2001;Berg et al, 2002). No studies have attempted to compare the molecular attributes of different invasive species to determine if patterns of invasion are predictable.…”
Section: Introductionmentioning
confidence: 99%
“…As first supposed by Sprules et al (1990), Lake Ladoga and Neva Estuary (eastern Gulf of Finland, Baltic Sea) could serve a source for Bythotrephes invasion. This hypothesis has been supported by the genetic study of Bythotrephes confirming the existence of the Lake Ladoga -Neva Estuary -Gulf of FinlandLaurentian Great Lakes invasion corridor (Berg et al 2002). Natural vectors, such as fish (Jarnagin et al 2000) and waterfowl (Charalambidou et al 2003), can play a role in the dispersal of Bythotrephes resting eggs.…”
Section: Bythotrephes Longimanusmentioning
confidence: 84%
“…In summer 1998 C. pengoi was found in Lake Ontario, snagged on sport fishing lines (MacIsaac et al 1999). Most likely this is a question of secondary introduction by ships ballast waters from the eastern Baltic via an existing invasion corridor, identified in case of Bythotrephes invasion by Berg et al (2002). Recent genetic study by Cristescu et al (2001) demonstrated that the source population of Cercopagis in North American Great Lakes is most likely originated from the Baltic Sea population, namely Neva Estuary (eastern Gulf of Finland).…”
Section: Cercopagis Pengoimentioning
confidence: 99%